PREPARASI BENTONIT ALAM MENJADI NANO PARTIKEL - Bukit, Nurdin; Ginting, Eva Marlina; Harahap, Mukti Hamjah (JURNAL PENELITIAN SAINTIKA, 2014)
The purpose of this study is the manufacture of natural bentonite into  nano  particles  and  is  used  as  a  filer  on  thermoplastic  high-density polyethylene  (  HDPE  )  .  The  method  used  in  the  manufacture  of  nanoparticles  of  bentonite  are  two  ways  ;  The  first  synthesis  method  using surfactant  cetyl  trimethyl  ammonium  bromide  (  CTAB  )  and  the  second way  in  ballmill  for  10  hours  .  Characterization  of  the  particle  size analyzer  (  PSA  )  ,  morphological  analysis  with  scanning  electron microscope ( SEM ) and analysis of the structure by X  -  ray diffraction ( XRD  )  was  performed  .  Nano  particles  with  variation  of composition  of natural  bentonite  (  2  ,  4  ,  6  ,  8  ,  10  %  w  t)  blends   with  HDPE  and compatibilizer  PE  -  g-  MA  on  the  appliance  s  internal  mixer  at  a temperature  of  150oC  and  laboplatomil  rate  of  60  rpm  for  10 minute.Berdasarkan PSA analysis and X  -  ray , natural bentonite having an average size of 75 nm for synthesis with CTAB , and 97.5 nm for the ball  mill  .  from  the  results  of  XRD  analysis  of  minerals  crystoballite  ( SiO2 ) and phase annite ( Al3.448Fe3K0.99Na  0.01O12Si  2.552  ) . In testing the mechanical  properties  of  the  resulting  increase  in  tensile  strength  and breaking up the composition perpajangan 2 to 6 % and a decline in the composition  of  8  %  .  The  results  of  SEM  analysis  showed  that homogeneous  mixing  of  ingredients  and  the  bentonite  particle agglomeration on the composition of 10 % wt.